Phyto-Fabrication Tribulus terrestris Mediated Iron Oxide Nanoparticles: A Promising Approach of Antioxidant and Anticancer Activities via in vitro and in silico Studies - Ranjani Renugopal; Thirunavukkarasu Palaniyandi; Barani Kumar Rajendran; Senthilkumar Kaliamoorthy; Maddaly Ravi; Gomathy Baskar; Mugip Rahaman Abdul Wahab; Hemapreethi Surendran; Mahalakshmi Nannan; Manojkumar Govindaraj; Asha Sivaji; Wahidah H. Al-Qahtani; et al. (Frontiers in Bioscience-Landmark, 2025)
Background: Plant-mediated iron nanoparticles are increasingly utilized in biomedical and health applications due to their biocompatibility and nontoxicity. The therapeutic characteristics of these nanoparticles are extensively diverse. Methods: In this study, iron nanoparticles synthesized from Tribulus terrestris were characterized using various techniques, including Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-visible spectroscopy, vibrating sample magnetometry (VSM), and X-ray diffraction (XRD) analysis. Antioxidant properties were assessed using the hydrogen peroxide (H2O2) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assays. Anti-inflammatory activity was evaluated through protein denaturation studies. Antimicrobial activity was tested against wound pathogens. The effects of anticancer and wound healing were investigated using HCT-116 (colon cancer) and MG-63 (osteosarcoma) cells. Molecular docking studies were performed to assess the binding affinity of Tribulus terrestris bioactive compounds with proteins involved in the Adenomatous polyposis coli (APC) pathway of colon cancer. Results: The Tribulus terrestris-mediated Fe3O4 nanoparticles exhibited a peak at 290 nm using UV-visible spectroscopy. SEM and TEM analyses revealed that the nanoparticles were aggregated with an average size of 29 ± 0.24 nm. XRD analysis indicated a cubic crystalline structure. FTIR spectroscopy identified the biomolecules involved in the synthesis, and VSM confirmed a magnetic saturation of 14.75 emu/g. The antioxidant activity was demonstrated with DPPH (65.5%) and hydrogen peroxide (65.56%) assays at a dosage of 50 μg/mL, demonstrating a significant inhibition. The protein denaturation assay revealed a maximum inhibition of 54.57%. Lactobacillus had the strongest antibacterial activity at a concentration of 100 μg/mL, with an inhibitory zone of 35 mm. The anticancer assays showed IC50 values of 25.95 μg/mL for colon cancer (HCT-116) and 35.36 μg/mL for osteosarcoma (MG-63), indicating significant cytotoxicity, particularly against colon cancer cells. The nanoparticles also demonstrated effective regulation of cell migration at 50 μg/mL. Molecular docking studies revealed strong binding affinities between Tribulus terrestris compounds and APC pathway proteins relevant to colon cancer. Conclusion: This research underscores the potential of Tribulus terrestris-mediated iron nanoparticles as a sustainable and eco-friendly approach with significant antioxidant and anticancer properties, especially in combating colon cancer. The findings highlight their effectiveness in reducing oxidative stress, inhibiting cancer cell proliferation, and enhancing wound healing.